Market strategy for Ben and Jerry's homemade, Inc. into Singapore. - Goh, Mei Fern. (2013)
This project focuses on the formulation of market strategies for Ben & Jerry’s Homemade, Inc. in Singapore. Section A consists of research objectives and methodology. Section B gives an introduction on ice cream and yogurt. Section C discusses the company profile of Ben & Jerry’s Homemade, Inc.. In Section D, we analyze the Macroenvironment which consists of socio-cultural environment, economic environment, ecological environment, political and legal environment, as well as technological environment. In Section E, we discuss the Microenvironment which includes customers, competitors, distribution, company and public. Finally, in Section F, we make recommendations on the market strategies for Ben & Jerry’s ice cream and yogurt.